Anonymity handling and sensor object modeling for pervasive environments using VISA processing - Radhamani, G.; Vanitha, K.; Amphawan, Angela (IJITCS, 2014)
Pervasive computing devices are configured for anywhere at any time services to adapt the changes in the dynamic environment with respect to the user mobility.The paper proposes a salient model for a log based anonymity handling in pervasive networks.The model defines a resource registry and sensor object modeling.Associability between the nodes are configured with an allied user interface in the environment.Resource registry refers to a record of information about the sensor nodes.A log book is maintained to keep track of the service discovery issues.New device enquiry, registration and adaption are major issues in such pervasive devices.These issues lead to unacknowledged communication that causes anonymity.This paper defines and discusses the presence of anonymity in pervasive environments due to aforementioned issues.